2022
DOI: 10.1038/s41598-022-17271-3
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of kinase domain mutations in BCR::ABL1 leukemia by ultra-deep sequencing of genomic DNA

Abstract: The screening of the BCR::ABL1 kinase domain (KD) mutation has become a routine analysis in case of warning/failure for chronic myeloid leukemia (CML) and B-cell precursor acute lymphoblastic leukemia (ALL) Philadelphia (Ph)-positive patients. In this study, we present a novel DNA-based next-generation sequencing (NGS) methodology for KD ABL1 mutation detection and monitoring with a 1.0E−4 sensitivity. This approach was validated with a well-stablished RNA-based nested NGS method. The correlation of both techn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The resulting libraries included three biological replicates per biomarker. They were sequenced on the Ion S5 System platform (Life Technologies, Thermo Fisher Scientific) with an estimated depth of 500,000× per amplicon, as previously described ( 24 , 29 , 30 ). The LiqBio-MRD test demonstrated a potential VAF sensibility below 10 −4 ( 24 ).…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…The resulting libraries included three biological replicates per biomarker. They were sequenced on the Ion S5 System platform (Life Technologies, Thermo Fisher Scientific) with an estimated depth of 500,000× per amplicon, as previously described ( 24 , 29 , 30 ). The LiqBio-MRD test demonstrated a potential VAF sensibility below 10 −4 ( 24 ).…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…Though there are many good myeloid panels available on the market from Thermofisher, Qiagen, Illumina, Archer, etc., they are not enriching the transcript P210 or P190 before sequencing. A recent study that used a DNA-based method to detect kinase domain mutations found that the method had a 92% sensitivity and an 81.6% specificity 49 . The use of DNA as a starting material may have contributed to a decrease in the assay's specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast by using DNA both ABL1 and BCR::ABL1 alleles would be sequenced—which would usually result in an inferior LoD because the number of BCR::ABL1 alleles (present only in leukemic cells) are far fewer than the number of ABL1 alleles (present in both leukemic and normal cells). Use of high sensitivity techniques like error-corrected NGS or digital PCR might theoretically enable this issue to be circumvented [ 144 ], and indeed the utility of DNA-based targeted dPCR for T315I has been described in patients with advanced disease [ 145 ], but a systematic comparison would be needed before generally endorsing DNA-based strategies.…”
Section: Bcr::abl1 Mutations and Mechanisms Of Resistance To Tkismentioning
confidence: 99%